Arade: revista do Arquivo Municipal de Lagoa, 2023 (2) - Ribeiro, Fernanda (Tábula, 2024)
Reseña del número 2 de ARADE: revista del Archivo Municipal de Lagoa. Review of issue 2 of ARADE: magazine of the Municipal Archive of Lagoa.